Data from: Effects of elevated carbon dioxide on male and female behavioural lateralisation in a temperate goby - Sundin, Josefin; Jutfelt, Fredrik (Dryad, 2018)
Behavioural abnormality in fishes has been proposed as a significant
threat of the increasing levels of carbon dioxide occurring in the oceans.
Negative effects of elevated CO2 have been reported for behaviours such as
predator-prey interactions, foraging, hearing and behavioural
lateralisation. Importantly, the effects vary greatly both within and
between species, and some recent studies have shown minimal effects of CO2
on behaviour. Whether the effect of CO2 also varies between males and
females is however virtually unexplored. According to resource allocation
theory, females are expected to be more sensitive to elevated CO2, meaning
that non-sex specific studies may overlook ecologically important
differences between the sexes. In this study, we investigated the possible
differences between males and females in their response to elevated CO2 by
performing behavioural lateralisation tests in adult temperate two-spotted
gobies Gobiusculus flavescens. We found that the strength of the side bias
(absolute lateralisation) was unaffected by the CO2 treatment, and there
was no difference between males and females. The control fish were
slightly right-biased in their behavioural asymmetry (mean relative
lateralisation of 14). Exposure to high CO2 affected this pattern, such
that treated fish were slightly left biased (mean relative lateralisation
of -10), regardless of their sex. The same results were obtained yet again
when the study was repeated during a second year. We discuss our results
in light of the great variation in lateralisation that has been reported
to depend on variables such as species, ecological settings and
environmental factors.
Sundin and Jutfelt 2018 CO2 lateralisationRaw data to reproduce the
analyses presented in Sundin and Jutfelt 2018.Data Sundin and Jutfelt goby
CO2 lateralisation.xlsx
Keywords: Teleost; Gobiusculus flavescens; pCO2; Anthropogenic; CO2 exposure